2011
DOI: 10.1111/j.1552-6569.2011.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Activation Changes in Patients Suffering from Post‐Stroke Arm Spasticity and Treated with Botulinum Toxin A

Abstract: Relief of post-stroke arm spasticity may be associated with changes at several hierarchical levels of the cortical sensorimotor system, including the prefrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 45 publications
(75 reference statements)
10
34
3
Order By: Relevance
“…BoNT application significantly relieved spasticity across paretic patients and this beneficial effect was associated with substantial reduction of activation in the most of previously active areas at W4. This BoNT-related reduction in the extent of the active sensorimotor networks is consistent with results of our pilot study reported by Tomášová et al [45] and a similar effect was reported by Manganotti et al [30]. We have previously hypothesized about the similarity of this phenomenon with motor recovery after stroke.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…BoNT application significantly relieved spasticity across paretic patients and this beneficial effect was associated with substantial reduction of activation in the most of previously active areas at W4. This BoNT-related reduction in the extent of the active sensorimotor networks is consistent with results of our pilot study reported by Tomášová et al [45] and a similar effect was reported by Manganotti et al [30]. We have previously hypothesized about the similarity of this phenomenon with motor recovery after stroke.…”
Section: Discussionsupporting
confidence: 90%
“…Our BoNT-off data (W11) yielded a pattern nearly similar to W4. This particular trend differs from Tomášová et al [45] where BoNT-off data (W11) again resembled the pre-BoNT examination (W0). Synergic effect of BoNT application and physiotherapy in less severely affected patients may play a crucial role in this phenomenon.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Some studies have investigated the effects of Botulinum Toxin A (BoNT-A) on spasticity in patients post-stroke. They have shown a decrease in activation of the posterior cingulate cortex and precuneus [68] following treatment and a decrease in activation in contralateral frontoparietal areas including inferior frontal, post-central and middle frontal gyrus, with activation limited to midline and contralateral sensorimotor cortices [69].…”
Section: Neuroimagingmentioning
confidence: 99%